Editorial Introduction: Reflecting on Our Shared Educational Futures: A Global Need to Belong for Transformative Learning - Reed, Erica; German, Celina; Geraghty, Patricia; Brown, Kelly; Carmichael, Jami (Current issues in education (Tempe, Ariz.), 2025)
In this editorial introduction to the Fall 2025 issue of Current Issues in Education, we explore belonging as the relational and systemic foundation of educational transformation. Building on prior discussions of equity and redesign through care, this issue highlights how belonging and agency operate across micro, meso, and macro levels—from teacher identity and classroom collaboration to institutional leadership and policy design. Across the eight articles published in this issue, authors demonstrate that transformation is sustained not by compliance or reform cycles, but by relationships that cultivate trust, capacity, and shared purpose. Together, these works illustrate how belonging can be institutionalized as both a human need and a policy imperative, shaping educational futures that are inclusive, adaptive, and rooted in connection.